ENT300 Business Plan : Easylicious Enterprise / Nur Hidayah Mohd Pauzi...[et al.] - Mohd Pauzi, Nur Hidayah; Ismail, Nur Hazwanie; Othman, Ruzee; Mohd Nizam, Nur Uzma; Roslee, Nur Hanna Syamila; Yahaya, Nur Farah Azmina; Mat Rashid, Nur Farhana (2020)
Purpose of Business Plant o allow entrepreneur to view and evaluate the proposed venture in an objective, critical and practical manner. With business plan, entrepreneurs can effectively plan to achieve his or her goal. The business plan providing elements that entrepreneur need to follow and solutions when risk management happen in the business. Be a guideline for managing the business. Entrepreneur uses the business plan as a reference to achieve the objective and purpose of the business. The detailing of business plan can be procedure of manufacturing production, guiding the timeline of produce and selling product and to ensure the businesses going smoothly and efficient. To convince relevant parties of the investment potential of the project. If the risk management are lower, investors can trust the business can be success and feeling safe to invest for getting back the dividend when business already operated.